How Reattachment to Work and Talent Retention Promote Proactive Behavior: The Mediating Role of Autonomous Motivation in Indonesia’s Leasing Industry - Elga Vania Sihaloho; Dita Oki Berliyanti; B Medina Nilasari (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2026)
Purpose: This study examines the effects of reattachment to work and talent retention on employees’ proactive behavior, with autonomous motivation serving as a mediating variable.Method: This study employed a quantitative research approach and used purposive sampling. Data were collected through structured questionnaires administered to full-time employees of leasing companies in Greater Jakarta who had at least one year of work experience. A total of 163 valid responses were analyzed using Structural Equation Modeling (SEM).Results: The findings indicate that reattachment to work and talent retention have significant positive effects on employees’ proactive behavior. Both variables also positively influence autonomous motivation, which, in turn, significantly enhances proactive behavior. Furthermore, autonomous motivation significantly mediates the relationship between reattachment to work and proactive behavior, as well as the relationship between talent retention and proactive behavior.Practical Implications for Economic Growth and Development: The findings demonstrate that strengthening employees’ psychological readiness to resume work and implementing effective talent retention practices can foster proactive behavior. These efforts may contribute to improved service quality, greater organizational competitiveness, and sustainable economic development.Originality/Value: This study integrates reattachment to work, talent retention, autonomous motivation, and proactive behavior into a unified conceptual model. It extends previous research by demonstrating the mediating role of autonomous motivation in explaining how employees’ psychological readiness and organizational talent retention practices foster proactive behavior. The study also provides empirical evidence from Indonesia’s leasing industry, a highly competitive sector that has received limited scholarly attention.